1984
DOI: 10.1093/geronj/39.3.264
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullary Catecholaminergic Activity Increases with Age in Male Laboratory Rodents

Abstract: In this report, we have examined the effects of aging on adrenomedullary catecholaminergic activity by evaluating the levels of activity of adrenal dopamine-beta-hydroxylase (DBH) in three species of laboratory rodents. Groups of male Fischer 344 rats (3-, 18-, and 28-month-old), Chinese hamsters (4- and 30-month-old), and Mongolian gerbils (3- and 26-month-old) were killed, and their adrenal DBH activities were measured by a sensitive radioenzymatic method. The results indicated that adrenomedullary DBH activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
0
11
1
Order By: Relevance
“…et al, 1995;Seals and Dinenno, 2004), and sustained elevation of catecholaminergic activity requires increased levels of catecholamine biosynthesizing enzymes in the adrenal medulla and peripheral sympathetic ganglia. Our laboratory along with others have reported that TH and DβH mRNA, protein levels and enzyme activities are two-to three-fold higher in the adrenals of senescent rats compared with younger animals (Banerji et al, 1984;Kedzierski and Porter, 1990;Tumer et al, 1999;Tumer et al, 1992;Tumer and Larochelle, 1995;Voogt et al, 1990). The underlying mechanisms are not fully understood, but it seems that increased activity of the sympathetic nervous system and the elevated amount of acetylcholine released from preganglionic sympathetic nerve terminals innervating the chromaffin cells of the adrenal medulla mediate, at least partially, the upregulation of TH and DβH (Dogan et al, 2004;Tumer et al, 1999).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…et al, 1995;Seals and Dinenno, 2004), and sustained elevation of catecholaminergic activity requires increased levels of catecholamine biosynthesizing enzymes in the adrenal medulla and peripheral sympathetic ganglia. Our laboratory along with others have reported that TH and DβH mRNA, protein levels and enzyme activities are two-to three-fold higher in the adrenals of senescent rats compared with younger animals (Banerji et al, 1984;Kedzierski and Porter, 1990;Tumer et al, 1999;Tumer et al, 1992;Tumer and Larochelle, 1995;Voogt et al, 1990). The underlying mechanisms are not fully understood, but it seems that increased activity of the sympathetic nervous system and the elevated amount of acetylcholine released from preganglionic sympathetic nerve terminals innervating the chromaffin cells of the adrenal medulla mediate, at least partially, the upregulation of TH and DβH (Dogan et al, 2004;Tumer et al, 1999).…”
Section: Discussionmentioning
confidence: 57%
“…We, as well as others, have reported that mRNA, protein levels and enzyme activity of tyrosine hydroxylase (TH), the rate-limiting enzyme in catecholamine biosynthesis, are two-to three-fold higher in the adrenals of senescent rats compared with younger animals (Kedzierski and Porter, 1990;Tumer et al, 1992;Tumer and Larochelle, 1995;Voogt et al, 1990). In addition, dopamine beta-hydroxylase (DβH) is also upregulated in the adrenal medulla with age (Banerji et al, 1984;Tumer et al, 1999) and circulating catecholamines are elevated in both senescent humans and laboratory animals due to increased synthesis and release of these hormones from sympathetic ganglia and adrenals (Avakian et al, 1984;Esler M. et al, 1981;Hoeldtke and Cilmi, 1985;Ito et al, 1986;Ziegler et al, 1976). In contrast, aging has an opposite effect on hypothalamic TH biosynthesis.…”
Section: Introductionmentioning
confidence: 96%
“…Although there are no data at the present time comparing age-related changes in the phasic release of epinephrine and norepinephrine immediately before the corticosterone surge, a general increase in catecholamine synthesis and release has been reported with age (24,25). In addition, other blood-borne factors, such as PRL and opioid peptides, have been shown to influence corticoid release in vivo (26) and in vitro (27).…”
Section: Discussionmentioning
confidence: 60%
“…Regarding the age‐associated reduction of mRNA levels of DBH in the adrenal glands, our results do not support previous reports in which DBH activity in adrenal medulla showed a progressive age‐related increase in rats, Chinese hamsters and Mongolian gerbils (Kvetnansky et al . 1978; Banerji et al . 1984).…”
Section: Discussionmentioning
confidence: 99%